ANALISIS PENGARUH KINERJA ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE (ESG) TERHADAP ABNORMAL RETURN (Studi pada Perusahaan Indonesia dan Malaysia yang mengungkapkan ESG score dan terdaftar pada Bursa Efek Indonesia dan Bursa Malaysia Tahun 2010-2015) - Syafrullah, Saddek; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2017)
The purpose of this study is to analyze the influence of environmental performance, social performance, and corporate governance to abnormal return as measured by environmental, social, and governance (ESG) disclosure score.The populations of this study are companies in Indonesia and Malaysia listed on the Indonesia Stock Exchange and Kuala Lumpur Stock Exchange (KLSE) that revealed the Environmental, social, and governance (ESG) disclosure score in the year 2010-2015. This study used secondary data with total sampel is 192 data as determined by purposive sampling method. Test analysis using data panel eviews with fixed effect model that has been tested by Chow test (F test) and Hausman test.The result of this study show that environmental performance did not has significant but positive influence to the abnormal return. Social performance and corporate governance have significantly and positively influence to the abnormal return. These results correspond with the legitimacy and stakeholders theory.